Western disturbances and climate variability: a review of recent developments - K. M. R. Hunt; K. M. R. Hunt; J.-P. Baudouin; A. G. Turner; A. G. Turner; A. P. Dimri; A. P. Dimri; G. Jeelani; Pooja; R. Chattopadhyay; R. Chattopadhyay; F. Cannon; et al. (Weather and Climate Dynamics)
Western disturbances (WDs) are synoptic-scale weather systems embedded within the subtropical westerly jet. Manifesting as upper-level troughs often associated with a lower-tropospheric low over western or northern India, they share some dynamical features with extratropical cyclones. WDs are most common during the boreal winter (December to March), during which they bring the majority of precipitation – both rain and snow – to the western Himalaya, as well as to surrounding areas of north India, Pakistan, and the Tibetan Plateau. WDs are also associated with weather hazards such as heavy snowfall, hailstorms, fog, cloudbursts, avalanches, frost, and cold waves.